Respon Pemberian Multi Mineral Blok (MMB) Terhadap Pertambahan Bobot Badan Sapi Bali - Farizal, Farizal (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2008)
The  objective  of  the  study  was  to  observe  response  of  feeding Bali  cattle multi  mineral  block (MMB) as a feed supplement on the body weight gain of Bali cattle. Nine male Bali cattle aged between 1 – 1,5 years were allotted in the Randomized Block Design consisted of 3 treatments and 3 blocks of body weight.  Parameters  measured were  roughage  intake,  absolute  and  relative  body  weight  and  feed efficiency. .Result  of  this  experiment  shows  that feeding  MMB  has  influence  (  P  <  0,05  )  on  roughage intake and body weight gain ( P < 0,01 ).  Duncan multiple  range test shows that body weight gain of cattle feed treatment R 1 and R 2 was high than those had treatment R0. It can be concluded that feeding MMB as a supplement could increase body weight gain of Bali Cattle.